8 femmes 8 women - Ozon, Francois 1967-; Thomas, Robert
A wealthy industrialist is found murdered in his home while his family gathers for the holiday season. The house is isolated and the phone lines have been cut. Eight women are his potential murderers. Each is a suspect and each has a motive.